TANGGUNG JAWAB HUKUM NOTARIS TERHADAP AKTA AUTENTIK YANG DIBUAT DIHADAPANNYA (ANALISIS PUTUSAN NOMOR 2022 K/PDT/2013) - Pamitama, Laberqi (UNES Law Review, 2020)
The Notary Deed in Article 1866 and Article 1867 of the Civil Code states that the Notary Deed is written evidence. In carrying out its duties, a Notary must be professional, this is stated in Article 16 letter of the Law on Notary Position. This research is a descriptive analytical study. The approach used in this research is a normative juridical approach. Based on the results of research and discussion, it can be concluded that: First, the form of Notary's legal accountability to the Authentic Deed made before him is the responsibility for the material correctness of the deed, then civil sanctions are imposed for errors that occur in the construction of illegal acts. Actions against the law in this case are active or passive. As a form of notary responsibility in the field of civil law, sanctions in the form of compensation, compensation and interest will be imposed as a result of which the Notary will receive from the lawsuit of the parties if the deed only has evidence as an underhand deed or the deed is null and void by law. Second, the notary can be responsible for the Authentic Deed made before him, it can be from reimbursement of expenses, compensation or interest that can be sued against the Notary based on a legal relationship between the Notary and the parties before the Notary. If there is a party who feels aggrieved as a direct result of a notary deed, then the person concerned can sue the notary publicly. In the case of a lawsuit due to an act against the law, Article 1365 of the Civil Code applies. In this case the Cassation Petitioners were rejected, so the Cassation Petitioners were sentenced to pay court fees at this cassation level.